A Better Learning Community: Mixed-Methods Reveal Medical Student Preferences with Implications for Learning Community Design and Implementation. (May 2021) - Vuk, Jasna; McKee, Steven; Tariq, Sara; Mendiratta, Priya
Background: Medical school learning communities benefit students. The College of Medicine (COM) at the University of Arkansas for Medical Sciences (UAMS) provides medical students with academic, professional, and personal support through a learning community (LC) made of 7 academic houses. Objectives: To evaluate the effectiveness of the academic house model at UAMS utilizing a mixed-methods survey. The aims were to: (1) assess student experience and satisfaction with academic houses, (2) describe the realms of advising and guidance, and (3) identify areas for improvement. Method: An online survey was assigned to 723 COM students (all students enrolled, first through fourth years) at UAMS in March 2019. The survey was comprised of 25 items (10 multiple-choice, 8 on the Likert scale, and 7 open-ended questions). Data was depicted using frequency and percentages and/or thematic review of free-form responses. Results: The survey response rate was 31% (227 students). The majority of students responding (132, 58.1%) attended 2 or more face-to-face meetings with the faculty advisor within the preceding year. However, 27 (11.9%) students did not have any meetings. Approximately two-thirds of the respondents were satisfied or very satisfied with the guidance and direction provided by their advisors [very satisfied (n = 83; 36.6%); satisfied (n = 77; 33.9%)]. Themes that emerged from student generated areas for improvement include time constraints, advisor/advisee interest mismatch, and perceived inadequacy of advising content/connections. Conclusions: This study confirms the effectiveness of the LC model for advising and mentoring in the COM at UAMS. Uniquely, this study identifies not only learners' satisfaction with their LC but also highlights areas for improvement which are widely generalizable and important to consider for institutions with or planning to start an LC.